Ionising radiation immediately impairs synaptic plasticity-associated cytoskeletal signalling pathways in HT22 cells and in mouse brain: an in vitro/in vivo comparison study. - Stefan J Kempf (Public Library of Science (PLoS), 2014)
Patients suffering from brain malignancies are treated with high-dose ionising radiation. However, this may lead to severe learning and memory impairment. Preventive treatments to minimise these side effects have not been possible due to the lack of knowledge of the involved signalling pathways and molecular targets. Mouse hippocampal neuronal HT22 cells were irradiated with acute gamma doses of 0.5 Gy, 1.0 Gy and 4.0 Gy. Changes in the cellular proteome were investigated by isotope-coded protein label technology and tandem mass spectrometry after 4 and 24 hours. To compare the findings with the in vivo response, male NMRI mice were irradiated on postnatal day 10 with a gamma dose of 1.0 Gy, followed by evaluation of the cellular proteome of hippocampus and cortex 24 hours post-irradiation. Analysis of the in vitro proteome showed that signalling pathways related to synaptic actin-remodelling were significantly affected at 1.0 Gy and 4.0 Gy but not at 0.5 Gy after 4 and 24 hours. We observed radiation-induced reduction of the miR-132 and Rac1 levels; miR-132 is known to regulate Rac1 activity by blocking the GTPase-activating protein p250GAP. In the irradiated hippocampus and cortex we observed alterations in the signalling pathways similar to those in vitro. The decreased expression of miR-132 and Rac1 was associated with an increase in hippocampal cofilin and phospho-cofilin. The Rac1-Cofilin pathway is involved in the modulation of synaptic actin filament formation that is necessary for correct spine and synapse morphology to enable processes of learning and memory. We suggest that acute radiation exposure leads to rapid dendritic spine and synapse morphology alterations via aberrant cytoskeletal signalling and processing and that this is associated with the immediate neurocognitive side effects observed in patients treated with ionising radiation.